Humanistic Values in the Holistic-Integrative ISMUBA (Al-Islam, Kemuhammadiyahan, and Arabic Language) Curriculum Based on the Kurikulum Merdeka (Independent Curriculum) Framework: A Literature Review Using Carl Rogers’ Humanistic Approach - Nazmi Nazmi; Fikri Haikal (al-Afkar, Journal For Islamic Studies, 2026)
Al-Islam, Kemuhammadiyahan, and Arabic Education (ISMUBA), as the spiritual core of Muhammadiyah education, continues to face challenges due to the dominance of normative–cognitive approaches that emphasize memorization and comprehension of theoretical texts, thereby insufficiently engaging students’ personal experiences and value internalization. The implementation of the Merdeka Curriculum requires a paradigmatic shift in learning toward a student-centered approach that is responsive to the diversity of individual potential. This study aims to examine humanistic values within the holistic, integrative ISMUBA curriculum based on the Merdeka Curriculum framework through the perspective of Carl Rogers’ humanistic psychology, particularly the values of monotheism (tawhid), freedom, responsibility, and moral awareness. This study employs a qualitative approach using a library research method. Data were collected through a systematic review of literature, including ISMUBA curriculum documents, Carl Rogers’ works, Merdeka Curriculum policy documents, and relevant scientific journals. The data were analyzed using a descriptive qualitative method with an inductive reasoning pattern. The findings indicate that Rogers’ humanistic values, such as self-actualization, empathy, meaningful learning, and unconditional positive regard, demonstrate conceptual alignment with the vision of Islam Berkemajuan in shaping the concept of insan kamil (the holistic human being). The integration of these values is manifested through three primary pathways: intracurricular learning activities, the Muhammadiyah, Pancasila Student Profile Strengthening Project (P5), and religious practices along with school cultural habituation. Furthermore, the implementation of humanistic values is reflected in differentiated learning practices (Teaching at the Right Level), the utilization of digital technology, and reflective–dialogical approaches that respect students’ individuality. This study concludes that the integration of Carl Rogers’ humanistic values within the ISMUBA curriculum under the Merdeka Curriculum framework functions as an instrument for the humanization of Islamic education, liberating students from rigid dogmatism and fostering graduates who are balanced in intellectual intelligence, spiritual maturity, and moral integrity.